Differences in Regional Media Responses to China’s Holistic Tourism: Big Data Analysis Based on Newspaper Text - Chao Wang (IEEE, 2020)
Holistic tourism is an important strategy to promote tourism development and has been widely concerned by the academic community. Newspaper media is an important thought output port of the local government. Newspaper media reports can reflect each regional response to the holistic tourism strategy to a certain extent. By investigating newspaper text using big data analysis, the differences in regional media responses to holistic tourism provide new research perspectives for scholars in the fields of global information, big data, and tourism. These differences also provide reference for policymakers in measuring the response of international media reports. Based on the full-text database of China National Knowledge Infrastructure newspaper, this study analyzes the situation of “holistic tourism” reported by different regional newspapers in China using content analysis and bibliometrics. From the perspectives of three dimensions of attention, importance, and focusing degrees, the coverage time of newspaper media in the eastern and the central regions of China is earlier than that in the western China. However, the newspaper media reports have increased in the western region after some years. From the media response index, China’s holistic tourism media response area has been increasing annually and rapidly expanding to 31 provinces in Mainland China, showing the characteristics of the east central part of the country being higher than the west. By designing the concept of media response index, this study provides a new research perspective for scholars from different fields and enriches the measurement and the theoretical systems of media response.